Automatic Vehicle Speed Control and Accident Detection and Messaging System - Sagar, J.; Rahul, H. R.; Varun, C.; Akshay, G. N.; Cleatus Thundiyil, Saneesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Road accidents have been very common in the present world with the prime cause being the careless driving. The necessity to check this has been very essential and different methods have been used so far. However, with the advancement in the technology, different governing bodies are demanding some sort of computerized technology to control this problem of over speed driving. At this scenario, we are proposing a system to detect the vehicle which are being driven above the given maximum speed limit that the respective roads or highway limits. And if the person did not control his speed there is a chance of accident. if accident occurs, the location of the accident spot will be sent to nearest hospital and police station via GSM module. Our project will provide an optimum solution to this draw back. An accelerometer can be used in a vehicle alarm application so that dangerous driving can be detected.
Keywords: Arduino; GSM; GPS; Sensors